Les « amazoones », des chimères du mouvement antispéciste ? - Nolwenn Veillard (Glad!)
Defined as a syncretism between feminism and antispeciesism, the femalist current aims to hybridize the two struggles to form a single one in defense of all “females”. Within the antispeciesist movement, the use of this political category, and the current’s essentialist aspirations, do not meet with unanimous approval. To better understand these tensions, the article first reviews the concept’s theoretical genealogy, looking at both its premises and its more contemporary developments. Then, based on the case study of a militant collective that claims a femalist identity, the article highlights the discursive appropriations made of these theoretical works on the scale of the organization and its activists, as well as the contrasting reception of this current within the antispeciesist movement itself.